Comparative study of tool path strategies in CNC machining for part with B-spline surfaces - Zainal Fahmi, Zainol Abidin; M. Nafis, O. Z. (Springer, Singapore, 2020)
CNC machines are widely used in production of various machinery components including turbine blades, impellers, rotors, propellers etc. Most of these components are built-up from free form surfaces which considered complex shapes and required proper set up for machining. This paper presents optimization of toolpath pattern for cutting parts with B spline surfaces in 4 axis machining. Generally the operation is carried out by using 4 axis machining methods which employs variable streamline operations in the finishing process. The appropriate selection of a toolpath pattern can significantly improve productivity and lead to lower production times. Different toolpath scenarios are simulated in CADCAM prior to real cutting process. In order to execute the comparative study of tool path strategies, all common cutting parameters (spindle speed, feed rate, tool diameter, plunge-rate, and depth of cut) are set to be constant. The toolpath strategies employed in this study includes helical or spiral, zig, zigzag and zigzag with lift. Cutting operation built-up and validation are performed through NX10, VERICUT and CNC machining. The objective is to optimize the machining process for B-spline model by selecting the shortest toolpath with maximum volume removal based on using variable streamline operation. The result indicates different tool path strategies based on the level of B spline curvature exhibit in the component.